ANALYSIS AND SOLUTIONS OF THE CURRENT SITUATION AND PROBLEMS OF ORGANIZING THE ACTIVITIES OF SMALL AND PRIVATE BUSINESS ENTITIES IN UZBEKISTAN (World Economics and Finance Bulletin, 2024)
The article considers information about the current state of small business and private business entities, their growth trends, and the article also shows the role of small business and private business entities in the current economy and their share in some sectors. The article describes the external and internal problems that are currently the most difficult for business entities and how to solve them. Additionally, the results of the survey conducted among entrepreneurs are also included in the analytical center of the article. Statistical indicators and results of econometric analysis are expressed in a convenient visual graphic form